Vitamin D level and glycemic control in type 2 diabetes mellitus - Alhussary, D. N.; Mohialdeen, S. K. (Regulatory Mechanisms in Biosystems, 2025)
Vitamin D’s effects outside the skeleton have garnered a lot of attention. A lack of vitamin D seems to be linked to the onset of type 2 diabetes and the metabolic syndrome. It has been shown that mild to severe vitamin D insufficiency raise s the risk of type 2 diabetes. This study aimed to study vitamin D levels in a group of T2DM patients and to investigate its relation with the degree of glycemic control. A case-control study was conducted in Mosul, Iraq, between October 2024 and January 2025, including 160 participants aged 35–60 years. Eighty individuals diagnosed with T2DM were compared with 80 age- and sex-matched healthy persons. Blood samples were collected after overnight fasting to determine levels of 25-hydroxy vitamin D [25(OH)D], fasting plasma glucose (FPG), hemoglobin A1c (HbA1c), parathyroid hormone (PTH), calcium, and phosphate. Vitamin D levels were substantially lower in T2DM patients (6.86 ± 2.3 0 ng/mL) than in controls. PTH levels were higher in T2DM patients. The levels of serum calcium and phosphate were lower in the diabetic group. We observed relationships between Vitamin D and both HbA1C and FPG in the T2DM group. Similar inverse connections were seen between calcium and blood sugar levels. The research hig h lights a reverse link between vitamin D and calcium levels with indicators of blood sugar control in patients with t ype 2 diabetes. The results emphasize how term high blood sugar levels can affect the metabolism of bone minerals and stress the need to keep track of indicators of bone health in people with diabetes.